Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi Kasus Pada Perusahaan JNE Cabang Lhokseumwe) - Khairina AR; Nada Julianda (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2020)
This study aims to determine the effect of Service Quality on Customer Satisfaction (a Case Study at JNE Company of Lhokseumawe City Branch). It is a quantitative descriptive study, and the population is all customers or consumers who use the JNE courier service in the Lhokseumawe City Branch, which is unlimited (infinite). The type of non-probability sampling used by researchers in this study is Accidental sampling. This study uses primary and secondary data obtained by distributing questionnaires to 100 respondents who were selected using a sample research technique based on chance, namely selecting respondents by visiting respondents and then selecting prospective respondents who are met by chance. The data analysis method used is a multiple linear regression method with the help of SPSS. The results show that physical evidence has a positive and significant effect on customer satisfaction at JNE companies, reliability has a positive and insignificant effect on customer satisfaction at JNE companies, responsiveness has a positive and significant effect on customer satisfaction at JNE companies, and assurance has a positive and insignificant effect on customer satisfaction. Customer satisfaction at JNE companies and empathy has a positive and significant effect on customer satisfaction at JNE companies.Keywords: Service Quality, Customer Satisfaction